THE ANALYSIS OF AMBIGUITY IN TV SERIES ENTITLED HOW I MET YOUR MOTHER - Ardhya, Ghea Raema Bella (2015)
The study entitled The Analysis of Ambiguity in TV Serie Entitled How I Met Your Mother is aimed to reveal the employment of ambiguity and to identify the context of situation lead to the use of the ambiguity in the script of How I Met Your Mother season 8. This study utilizes Stephen Ullmann's theory of ambiguity (2014) and Dell Hymes's theory of the context of situation (1974). The result of the analysis shows that the total number of the ambiguity found is 62 items; consist of 50 lexical ambiguities, one structural ambiguity, and eleven phonological ambiguities. Moreover, the use of ambiguity depends on various context of situation. Based on the result of discussion, ambiguity is mostly used in casual context and conversation. It emphasizes that ambiguity is an essential element in joke and pun. Keywords: ambiguity, sitcom, humor, context of situation